Molecular docking of triterpene glycoside compounds (cucurbitane, charantin and momordicin) in bitter gourd (Momordica charantia L.) fruit as anti-diabetes mellitus type 2 - Cristiannanda, Daniel; Hati, Dinda Mutiara; Hafid, Gina Mutia; Anggini, Joya Talitha; Setiawati, Luh Gede Elen; Putri, Mutiara; Chandra, Nabella Oktaviana; Auli, Winni Nur Auli; Saputro, Anjar Hermadi (Pharmacy Reports, 2022)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels due to impaired insulin secretion, insulin resistance, or both. Type 2 diabetes mellitus (T2DM) accounts for approximately 90% of all diabetes cases and remains a significant global health challenge. Current pharmacological treatments often have limited efficacy and adverse side effects, necessitating the exploration of safer, more effective antidiabetic agents. Momordica charantia (bitter melon) is a medicinal plant known for its hypoglycemic properties, attributed to bioactive compounds such as cucurbitane-type triterpenoid glycosides, charantin, and momordicin. This study evaluated the potential of cucurbitane, charantin, and momordicin as antidiabetic agents for T2DM using molecular docking simulations. The crystal structure of aldose reductase (PDB ID 2HV5) was obtained from the Protein Data Bank, and AutoDock Tools 1.5.7 was used for docking studies. The binding affinities and interaction patterns of the test compounds were compared with zopolrestat, a standard ligand. Cucurbitane exhibited the lowest binding free energy (-11.70 kcal/mol), indicating the strongest interaction with the 2HV5 protein. All compounds demonstrated similarities in their interactions with key amino acid residues, suggesting comparable biological activity. These findings highlight cucurbitane’s potential as a lead compound for developing more effective antidiabetic therapies for T2DM.